Binary Gender Roles and Sexism: Explanation Based on Values and Personality - Soares, Ana Karla Silva; Leite, Júlia Juliana Santos; Rezende, Alessandro Teixeira; Freires, Leogildo Alves (Revista de Psicología, 2022)
This research aims to analyse to what extent and direction sexism, gender roles, human values ​​and personality are related, evaluating how the last two variables can explain this relationship. There were 213 participants, with a mean age of 27 years (18 to 60 years; SD = 9.48), most of them female (67.6%). They responded to the Good Sex Roles Inventory, Ambivalent Sexism Inventory, Basic Values ​​Questionnaire and Big Five Personality Factors Inventory. The results identified that only human values ​​positively explain hostile sexism (normative and suprapersonal) and benevolent (normative). And gender roles were explained both by personality traits (femininity —agreeableness, conscientiousness, and extraversion; masculinity —conscientiousness, neuroticism, extroversion, and openness) and by human values ​​(femininity— interactive; masculinity— achievement). It was concluded that evaluative priorities and personality traits play an important role in understanding ambivalent sexism and gender roles today.